A novel chronic advanced staged abdominal aortic aneurysm murine model - Lu, Guanyi (J Vasc Surg, 2017)
OBJECTIVE: The purpose of this study was to establish a reliable, chronic model of abdominal aortic aneurysm (AAA). MATERIALS AND METHODS: 120 eight-week old C56BL/6 male mice were equally divided into three groups: 1) BAPN Group: 0.2% 3-aminopropionitrile fumarate salt (BAPN) drinking water was provided to mice two days before surgery until the end of study. Sham aneurysm induction surgery was performed using 5 μl of heat de-activated elastase. 2) Elastase Group: Mice were given regular drinking water without BAPN. During aneurysm induction surgery, 5 μl of active form elastase (10.3mg protein/ml, 5.9units/mg protein) was applied on top of adventitia of infrarenal abdominal aorta for 5 minutes. 3) BAPN+Elastase Group: Mice were given both BAPN drinking water and active form of elastase application as above. On post-operative days 7, 14, 21, 28 and 100, aortic samples were collected for histology, cytokine array and gelatin zymography after aortic diameter measurement. RESULTS: Compared with Elastase group, BAPN+Elastase group had higher AAA formation rate (93% vs 65%, P < .01) with more advanced-staged AAAs (25/42 vs 1/40 for Stage II & III, P < .001). Aneurysms from the BAPN+Elastase Group demonstrated persistent long-term growth (221.5 ± 36.6%, 285.8 ± 78.6%, 801 ± 160% on day 21, 28 and 100 respectively, P ˂ .001), with considerable thrombus formation (54%) and rupture (31%) at the advanced stages of AAA development. Cytokine levels (pro-MMP9, IL-1β, IL-6, CCL-5, TREM-1, MCP-1 and TIMP-1) in BAPN+Elastase Group were higher than Elastase Group on day 7. After day 7, cytokine levels returned to baseline with the exception of elevated MMP2 activity. By histology, CD3⁺T cells in the BAPN+Elastase Group were elevated on days 28 and 100. CONCLUSIONS: A combination of oral BAPN administration and peri-aortic elastase application induced a chronic, advanced staged AAA with characteristics of persistent aneurysm growth, thrombus formation, and spontaneous rupture. Future studies should utilize this model, especially for examining tissue remodeling during the late stages of aneurysm development.